In Search of Saint John: Reinventing Tradition for Migrants and Tourists in Cabo Verde - Fêo Rodrigues, Isabel P.B. (Revista de Antropología Social, 2016)
Following the revitalization of a popular feasts such as San Jon in Cabo Verde, this article highlights how this traditional feast is co-produced by those who left their rural villages in search of a better life in the USA and those who stay hoping to enhance the emigrant’s desire to return. These collective events not only help to sustain a relationship with a homeland, they also contribute to the flows of emigrant remittances and a transnational flow of gift exchange. In between departing and returning, migrants revitalize traditions, contribute to the wellbeing of rural lifestyles, and become agents of economic and cultural investment in their homeland.